Failure Analysis of Plant Fibre-Reinforced Composite in Civil Building Materials Using Non-Destructive Testing Methods: Current and Future Trend - Najeeb M.I.; Syamsir A.; Amir S.M.M.; Khan T.; Sebaey T.A. (Taylor and Francis Ltd., 2024)
Natural plant fiber-reinforced composite (NFC) has become a preferred component in modern-day civil building construction materials because it offers, among others, an environment-friendly solution without compromising stringent engineering requirements. Such green-based composites have exhibited noteworthy level of competitiveness comparable to that of the existing commercially available nongreen materials. Furthermore, NFC can also be tailored to align with the desired functional attributes. However, lack of comprehensive guidelines and recommended applications of suitable methods to assess composite failure of such novel NFC have raised significant concerns. This paper provides a comprehensive review of the latest developments in nondestructive testing (NDT) that can be applied to investigate into NFC failures. The study further explores alternative nondestructive testing methods and technologies exhibiting potential use in plant fiber composites studies, hence paving the way to future investigation trends. Precise characterization of defects and identification of damages in NFCs present a major challenge, demanding application of advanced nondestructive testing (NDT) methodologies accompanied with expert interpretation. Findings in this review can be applied to identify and explore new areas of research to analyze failure modes and fractures in NFC by applying NDT or by integrating NDT with other advanced technologies including machine learning. 2023 The Author(s). Published with license by Taylor & Francis Group, LLC.